Chemical Characterization of Bioactive Compounds in Food Plants and Their Pharmaceutical Effects - Fiza Talat1, Vaneeza Arshad Mughal2, Noor-ul-Ain3, Tehseen Ali Jilani4, Sadaf Javaria3, Muhammad Ashraf5, Alia Mushtaq6, Muhammad Ishtiaq7 (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Bioactive compounds in food plants have garnered significant attention due to their potential health benefits and pharmaceutical applications. This review paper provides an extensive examination of the types and chemical characterization of bioactive compounds found in food plants. The review covers polyphenols, alkaloids, terpenoids, and glycosides, among others. Various methods of chemical characterization, including chromatography and spectroscopy techniques, are discussed in detail. The pharmaceutical effects of these bioactive compounds, such as anti-inflammatory, antioxidant, anticancer, antimicrobial, cardiovascular, and neuroprotective properties, are explored. Case studies of specific food plants, including turmeric, garlic, green tea, ginger, and berries, highlight the practical applications and benefits of these compounds. The paper concludes with a discussion on the challenges in characterizing bioactive compounds and the future prospects for research and pharmaceutical development.